Telaah Sanksi Pidana dalam Perspektif Filsafat - Yeni Widowaty (Jurnal Hukum, 2007)
Punishment problem in criminal law is related to criminal philosophy. this relationship can be seen from two sides, there is philosophy that focusing on why he gives punishment